Evaluating HbA1c reduction with protocol-driven drug therapy in early type 2 diabetes: a prospective analysis - Patkar, Namrata Vilas; Panikar, Vijay (International Journal of Research in Medical Sciences, 2025)
Background: Effective blood sugar control is critical to preventing complications in type 2 diabetes. While intensive drug therapy can improve glycemic outcomes, the long-term benefit of starting with aggressive regimens tailored to disease severity remains under investigation. Methods: This study categorized patients with type 2 diabetes into three groups based on initial HbA1c levels: Group 1 (mild, 7–9%), Group 2 (moderate, 9–11%), and Group 3 (severe, >11%). Treatment was escalated accordingly: triple therapy for Group 1, quadruple therapy for Group 2, and quintuple therapy for Group 3. The medication regimen included pioglitazone, metformin, dapagliflozin, teneligliptin, and gliclazide. HbA1c levels were tracked to assess glycemic improvement and therapy simplification over time. Results: All groups achieved significant reductions in HbA1c. Group 1 saw a 24.4% reduction, Group 2 a 29.0% reduction, and Group 3 a 51.7% reduction (p=0.001). Notably, many patients in Group 3 were able to simplify their medication regimens during follow-up, transitioning from five drugs to fewer agents while maintaining glycemic control (p<0.05). Conclusions: Tailored intensive therapy based on initial glycemic severity leads to significant HbA1c improvement. Starting with robust combination therapy and later reducing drug burden may be an effective, sustainable strategy in managing type 2 diabetes.